Investigation of the Effect of Resistance Training Applied Using Functional Exercise Band (TRX) and Body Weight Applied to Male Basketball Players Aged 15-17 on Selected Physical Characteristics - Sadettin Erol (Journal of Educational Issues, 2024)
This study was planned to investigate the effect of resistance training applied using functional exercise band (TRX) and body weight applied to male basketball players aged 15-17 on selected physical characteristics. 30 elite basketball players in the youth category of Turkey were included in the study. Athletes; 13 athletes with a mean age of 16.00±0.707 years in the control group (CG) and 17 athletes with a mean age of 16.05±0.747 years in the experimental group (EG) were randomly divided into two groups. The experimental group was given TRX suspension training for 8 weeks with routine basketball training (3 days/week), a total training time of 45 minutes. The control group only did routine basketball training. Pre-tests of 2 groups of 30 athletes (leg extension leg curl, push-ups, sit-ups, (20 m) sprint, vertical jump and agility were taken at the end of 8 weeks before the exercises. Fully repeated measures ANOVA were used to make separate comparisons for the pre and post-measurements in the 8-week training sessions for the experimental and control training groups. Pre- and post-measurements of the groups were compared.; According to the analysis of the data, a significant difference was observed in the values of leg extension, leg curl, push-ups, sit-ups and vertical jump tests (p < 0.05). In the comparison between the groups (20m), significant difference was observed between sprint and agilityt test values (p > 0.05). However, TRX suspension training has shown that it can better improve leg curl, push-ups, sit-ups, and vertical jump performances in basketball players’ objects.